The Impact of Green Recruitment and Selection Practices Mediated by Innovative Organizational Culture on Employee Performance - Emelia Santi Tamin (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study evaluates the impact of Green Human Resource Management (GHRM) practices on employee performance and innovation in Indonesia’s banking sector. It specifically explores how green recruitment and selection (GRS) fosters an innovative organizational culture (IOC), enhances sustainability, and improves organizational effectiveness. Design/Methodology/Approach – The study involved 150 purposively selected employees from PT Bank Kalteng. A quantitative approach was used, with data collected through an online questionnaire rated on a 1–5 Likert scale. Structural Equation Modeling (SEM) with SMART-PLS 3 analyzed the relationships among GRS, IOC, and employee performance (EP). Findings – Results show that GRS positively and significantly affects employee performance and IOC. Moreover, IOC mediates the relationship between GRS and employee performance, indicating that GRS enhances performance indirectly by promoting an innovative culture. This underscores the role of culture in amplifying the effects of GHRM. Conclusion and Implications – This study contributes to the limited empirical research on GHRM in regional banking by highlighting GRS as a driver of innovation and sustainability. It offers practical insights for banks seeking to align environmental sustainability with HR strategies to improve employee outcomes.